Prediction of Si contents to suppress the interfacial reaction in the SiCp 2014 Al composite - Lee, JC; 박성배; Seok, HK; Oh, CS; Lee, HI (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
Equilibrium Si contents required to prevent the interfacial reaction in the SiCp/2014 Al composite site were predicted using both theoretical calculations and experimental method. According to the results, equilibrium Si contents increased with increasing temperature; When the composite is exposed at temperatures below the solidus of the matrix, less than 1 at.% of Si was found to be sufficient in order to prevent the interfacial reaction. However, Si contents required to prevent the interfacial reaction were observed to increase substantially at temperatures near 600 degrees C such that more than 5 at.% of Si was required to prohibit the interfacial reaction even at 620 degrees C. Application of such results for designing the matrix alloy and selecting process parameters for the semi-solid forming were demonstrated. (C) 1998 Acta Metallurgica Inc.